PERAN GURU DALAM MEMOTIVASI PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV DI SD NEGERI RANDUSANGA KULON - Nuhyil Nur Baety Kartika Putri; Didik Tri Setiyoko; Laelia Nurpratiwiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe the role of teachers in motivating students in Pancasila education learning and describe the inhibiting and supporting factors of student learning motivation in Pancasila education. The method used in this study is a qualitative method through a case study approach. Data collection techniques used are interviews, observation and documentation. Data analysis methods used are collecting data, data reduction, data display (data presentation), verification. The validity used is source triangulation, technique triangulation. The targets used in this study are principals, teachers, and students. Based on the results of the study, it shows that the role of teachers in motivating students in Pancasila education learning is good. The role of teachers in motivating students in class IV education learning is (1) Making students active in learning activities (2) Creating a conducive classroom atmosphere (3) Creating learning methods (4) Increasing enthusiasm and passion in teaching (5) Giving awards or prizes (6) Creating activities that involve students in the classroom. For the inhibiting and supporting factors of student learning motivation in Pancasila education, the first supporting factor is (1) Teachers have a deep understanding of the Pancasila principles (2) Adequate curriculum (3) Conducive school environment. The second inhibiting factor is (1) Minimal teacher understanding of Pancasila values ​​(2) Inconsistency between the curriculum and student needs (3) Lack of support from the government in providing adequate resources.